Pragmatic adaptation – the main factor in achieving adequate poetry translation (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the problem of pragmatic adaptation in translation studies and its relation to the poetry translation. In addition, the role of pragmatic adaptation in ensuring the adequacy of the translation of poetry is determined. Detailed information about pragmatic adaptation is given and frequently used types of translation technique during pragmatic adaptation are determined. In the article, the author determines the most often used translation method for pragmatic adaptation of poetry translation oriented to the reader. In addition, the article analyzes the preservation of the meaning of national words and expressions in English translation of Kazakh poetry, as well as the correspondence of ideas and effects transmitted by the author of poetry. As a result, the adequacy of the meaning and emotional effect of translated poetry and the original was determined. Thus, it can be stated that pragmatic adaptation is a factor of adequate poetry translation.